2016
DOI: 10.3767/003158516x689819
|View full text |Cite
|
Sign up to set email alerts
|

Newly recognised lineages of perithecial ascomycetes: the new orders Conioscyphales and Pleurotheciales

Abstract: Phylogenetic analyses of DNA sequences from nuclear ribosomal and protein-coding loci support the placement of several perithecial ascomycetes and dematiaceous hyphomycetes from freshwater and terrestrial environments in two monophyletic clades closely related to the Savoryellales. One clade formed by five species of Conioscypha and a second clade containing several genera of uncertain taxonomic status centred on Pleurothecium, represent two distinct taxonomic groups at the ordinal systematic rank. They are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 92 publications
6
94
0
Order By: Relevance
“…Phylogenetic trees obtained from MP, ML, and Bayesian analyses yielded trees with similar overall topology at the subclass, order and family levels (data not shown) and this topology is in agreement with previous papers based on ML analysis using RAxML (Maharachchikumbura et al 2015, 2016, Réblová et al 2016. One of the most six parsimonious trees was chosen and is shown in Fig.…”
Section: Phylogenetic Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…Phylogenetic trees obtained from MP, ML, and Bayesian analyses yielded trees with similar overall topology at the subclass, order and family levels (data not shown) and this topology is in agreement with previous papers based on ML analysis using RAxML (Maharachchikumbura et al 2015, 2016, Réblová et al 2016. One of the most six parsimonious trees was chosen and is shown in Fig.…”
Section: Phylogenetic Analysessupporting
confidence: 88%
“…In phylogenetic analysis of in-group taxa and related fungal species from Sordariomycetes, P. garethii grouped in the order Fuscosporellales, sub-class Hypocreomycetidae and class Sordariomycetes (Boonyuen et al 2011, Maharachchikumbura et al 2015, 2016, Réblová et al 2016, Yang et al 2016. Parafuscosporella garethii clustered with the type species of the genus (P. moniliformis).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic trees obtained from ML, MP and Bayesian analyses yielded trees with similar overall topology at the order and family levels which are in agreement with previous studies (Boonyuen et al 2016, Réblová et al 2016, Yang et al 2016 ellipsoidal or slightly irregular shaped, 3860 × 25.537 μm (x ̅ = 48.5 × 30.5 μm, n = 40), dark brown to black, smooth, with pale brown cell at the apex and the base.…”
Section: Phylogenetic Resultssupporting
confidence: 80%
“…The taxa included in the phylogenetic analyses were selected and obtained from previous studies and GenBank (Maharachchikumbura et al 2015, Réblová et al 2016, Yang et al 2016. LSU and ITS gene regions were used for the combined sequence data analyses.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Réblová Réblová et al (2016b) introduced this genus with a hyphomycetous asexual morph. Molecular phylogenetic analyses showed that Melanotrigonum belongs in Pleurotheciaceae.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%